Conformational Tuning of Amylin by Charged Styrene-Maleic-Acid Copolymers. Issue 2 (30th January 2022) - Sahoo, Bikash R.; Souders, Christopher L.; Watanabe-Nakayama, Takahiro; Deng, Zhou; Linton, Hunter; Suladze, Saba; Ivanova, Magdalena I.; Reif, Bernd; Ando, Toshio; Martyniuk, Christopher J.; Ramamoorthy, Ayyalusamy
Graphical abstract: Highlights: The generation of morphologically and pathologically distinct amylin species is reported. Cationic SMAQA polymer drives the formation of amylin globulomer intermediates. Anionic SMAEA accelerates amyloid formation by suppressing the intermediates. Amylin species formed with the copolymers showed minimal deformity to zebrafish embryos. Abstract: Human amylin forms structurally heterogeneous amyloids that have been linked to type-2 diabetes. Thus, understanding the molecular interactions governing amylin aggregation can provide mechanistic insights in its pathogenic formation. Here, we demonstrate that fibril formation of amylin is altered by synthetic amphipathic copolymer derivatives of the styrene-maleic-acid (SMAQA and SMAEA). High-speed AFM is used to follow the real-time aggregation of amylin by observing the rapid formation of de novo globular oligomers and arrestment of fibrillation by the positively-charged SMAQA. We also observed an accelerated fibril formation in the presence of the negatively-charged SMAEA. These findings were further validated by fluorescence, SOFAST-HMQC, DOSY and STD NMR experiments. Conformational analysis by CD and FT-IR revealed that the SMA copolymers modulate the conformation of amylin aggregates. While the species formed with SMAQA are α-helical, the ones formed with SMAEA are rich in β-sheet structure. The interacting interfaces between SMAEA or SMAQA and amylin are mapped by NMR and microseconds all-atom MD simulation. SMAEA displayed π-π interaction with Phe23, electrostatic π-cation interaction with His18 and hydrophobic packing with Ala13 and Val17; whereas SMAQA showed a selective interaction with amylin's C terminus (residues 31–37) that belongs to one of the two β-sheet regions (residues 14–19 and 31–36) involved in amylin fibrillation. Toxicity analysis showed both SMA copolymers to be non-toxic in vitro and the amylin species formed with the copolymers showed minimal deformity to zebrafish embryos. Together, this study demonstrates that chemical tools, such as copolymers, can be used to modulate amylin aggregation, alter the conformation of species.